Positioning and telemetry from ROV survey PS122/3_31-17 on 2020-03-10, survey 1 - Anhaus, Philipp; Katlein, Christian; Matero, Ilkka; Nicolaus, Marcel; Arndt, Stefanie; Krampe, Daniela; Lange, Benjamin Allen; Regnery, Julia; Rohde, Jan; Schiller, Martin (In: Anhaus, P et al. (2023): Positioning and telemetry from remotely operated vehicle (ROV) surveys during the MOSAiC expedition 2019/20 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.952676, 2023)
The horizontal position of the remotely operated vehicle (ROV) during the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition between November 2019 and September 2020 was measured using an acoustic Long Base Line (LBL) positioning system (LinkQuest Pinpoint). The position was recorded in the SPOT.ON survey systems software (OceanModulesTM). The track was smoothed from initial acoustic fixes and cleaned for most obvious outliers. The position is in a floe-fixed, relative coordinate system (X, Y) with the origin (X=0 m, Y=0 m) at the ROV hole. A quality flag for the position is introduced based on the time to the closest fix with “1” indicating good positon (fix reached <= 3s), “2” medium position (fix reached > 3s & <= 5s), and “3” bad position (fix reached > 5s). Depending on the scientific aim, a position with quality flag “3” can still be useful. Vehicle depth was measured by the integrated pressure sensor and calibrated to 0 during pre-survey procedures, when the top side of the vehicle was at the same level as the water surface. Vehicle attitude (roll, pitch, heading) was measured with an onboard inertial measuring unit (IMU, Microstrain) with three axis accelerometer, magnetometer and gyroscope. Depth was measured by a pressure sensor (Keller A-21Y, Keller AG) included in the main electronics housing of the ROV.
Keywords: BEAST; MOSAiC expedition; Remotely operated vehicle (ROV); Sea ice